Influence of iodinated contrast media on the activities of histamine inactivating enzymes diamine oxidase and histamine N-methyltransferase in vitro - Kuefner, M. A.; Feurie, J.; Petersen, J.; Uder, Michael; Schwelberger, H. G. (Allergologia Et Immunopathologia, 2014)
Iodinated contrast media can cause pseudoallergic reactions associated with histamine release in significant numbers of patients. To clarify whether these adverse reactions may be aggravated by a compromised histamine catabolism we asked if radiographic contrast agents in vitro inhibit the histamine inactivating enzymes diamine oxidase (DAO) and histamine N-methyltransferase (HMT).Nine iodinated contrast agents were tested in vitro. Following pre-incubation of purified porcine kidney DAO and recombinant human HMT with 0.1-10mM of the respective contrast medium (H2O and specific inhibitors of DAO and HMT as controls) enzyme activities were determined by using radiometric micro assays.None of the contrast media irrespective of their structure showed significant inhibition of the activities of DAO and HMT. Pre-incubation of the enzymes with specific inhibitors led to complete inhibition of the respective enzymatic activity.The iodinated contrast media tested in vitro did not exhibit inhibition of histamine converting enzymes at physiologically relevant concentrations. However due to the in vitro character of this study these results do not directly reflect the in vivo situation.
EVALuna2:14327